Assessment of combined sewer overflows impacts under flooding in coastal cities - Helieh Abbasi (IWA Publishing, 2021)
Wastewater treatment plants (WWTPs) are among the most important infrastructures, especially in coastal cities with a risk of flooding. During intense floods, runoff volume may exceed the capacity of a WWTP causing plant failures. This paper investigates the impacts of flooding on combined sewer overflows (CSOs) in a WWTP in New York City. The impacts of CSOs after flooding are classified into four categories of health, economic, social, and environmental factors. Different factors are defined to evaluate the impacts of CSOs using multi-criteria decision-making of Preference Ranking Organization Method For Enrichment Evaluation and fuzzy technique for order performance by similarity to ideal solution. Since volume and depth were found to be the most significant factors for the CSO impact assessment, the Gridded Surface Subsurface Hydrologic Analysis model was run to compute flood depth and CSO volume under three treatment plant failure scenarios considering the Hurricane Sandy information. Sensitivity analysis revealed that the Total Suspended Solids (TSS), Biochemical Oxygen Demand (BOD), and dissolved oxygen have the highest impacts on CSO. Uncertainty analysis was applied to investigate CSO impact variation. Results show that evaluating the impacts of CSOs in different aspects can help improve the efficiency of flood planning and management during storms. HIGHLIGHTS The impacts of combined sewer overflows (CSOs) after flooding are classified into health, economic, social, and environmental factors.; Different factors are defined, and consequently, different impacts of CSOs are evaluated using multi-criteria decision-making methods of Preference Ranking Organization Method for Enrichment Evaluation and fuzzy Technique for Order Performance by Similarity to Ideal Solution.; Floodplain delineation and flood depth are obtained using the Gridded Surface Subsurface Hydrologic Analysis model.; Under different scenarios, full operation, total failure and partial failure are considered.;